A positive electrode material, a preparation method thereof, a positive electrode sheet, a battery, and a power utilization device
Patent Information
- Application Number
- CN202611501963.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
在电池循环过程中,界面处极易诱发持续性的副反应,导致阻抗随循环次数增加而持续累积,从而引发了电池容量快速衰减、倍率性能恶化等严重问题
[0020]如上所述的电池,所述电池为固态电池,所述固态电池包括固态电解质层,所述固态电解质层包括硫化物固态电解质;所述硫化物固态电解质包括Li2S-P2S5型硫化物固态电解质、thio-LISICON型硫化物固态电解质、硫银锗矿型硫化物固态电解质及其非晶态衍生物中的至少一种。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a positive electrode material and its preparation method, a positive electrode sheet, a battery, and an electrical device. Background Technology
[0002] In recent years, with the rapid development of electric vehicles, large-scale energy storage systems and consumer electronics, solid-state batteries have become a cutting-edge hot topic in global new energy academic research and industrialization due to their advantages such as high safety, high energy storage capacity, and wide environmental tolerance.
[0003] However, the actual performance of solid-state batteries is highly dependent on the interfacial compatibility and stability between the solid electrolyte and electrode materials, especially the high-voltage cathode materials. Studies have shown that there is a significant mismatch between existing solid-state electrolyte systems and cathode materials, particularly high-voltage cathode materials. During battery cycling, persistent side reactions are easily induced at the interface, leading to a continuous accumulation of impedance with increasing cycle count, resulting in serious problems such as rapid capacity decay and deterioration of rate performance.
[0004] Therefore, effectively improving the capacity characteristics and rate performance of solid-state batteries during cycling has become the key to driving solid-state batteries from the laboratory to practical deployment and commercial application. Summary of the Invention
[0005] This application provides a cathode material that, through reasonable structural design, can effectively improve the capacity characteristics and rate performance of solid-state batteries during cycling when applied to cathode sheets.
[0006] This application also provides a method for preparing a cathode material, used to prepare the above-mentioned cathode material.
[0007] This application also provides a positive electrode sheet comprising the above-mentioned positive electrode material, thereby effectively improving the capacity characteristics and rate performance of solid-state batteries.
[0008] This application also provides a battery including the above-mentioned positive electrode, thus the battery has the advantages of high capacity, good rate performance and good cycle performance.
[0009] This application also provides an electrical device including the aforementioned battery, thus the electrical device has the advantage of stable long-term output power.
[0010] This application provides a cathode material, including a core, a first coating layer, and a second coating layer; the first coating layer is disposed on at least a portion of the surface of the core, and the second coating layer is disposed on at least a portion of the surface of the first coating layer away from the core; wherein, the first coating layer includes an oxide electrolyte, and the second coating layer includes a halide electrolyte.
[0011] In the above-described cathode material, the oxide electrolyte has a mass percentage content of less than or equal to 10% in the cathode material; and / or, the halide electrolyte has a mass percentage content of less than or equal to 10% in the cathode material.
[0012] In the cathode material described above, the oxide electrolyte has a mass percentage content of 2% to 5% in the cathode material; and / or, the halide electrolyte has a mass percentage content of 2% to 5% in the cathode material; and / or, the thickness of the first coating layer is 5 nm to 20 nm; and / or, the thickness of the second coating layer is 10 nm to 100 nm.
[0013] As described above, the core of the cathode material has a Dv50 of 3μm to 5μm.
[0014] As described above, the oxide electrolyte comprises at least one of perovskite oxide electrolyte, garnet oxide electrolyte, NASICON oxide electrolyte, LISICON oxide electrolyte, and amorphous oxide; and / or, the halide electrolyte comprises at least one of Li3MX6 halide electrolyte, Li2MX4 halide electrolyte, Li6MX8 halide electrolyte, and amorphous halide; and / or, the core comprises at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium-rich manganese-based materials.
[0015] This application also provides a method for preparing the cathode material according to any one of the above claims, comprising the following steps: first ball milling the core and the oxide electrolyte to obtain an intermediate; second ball milling the intermediate and the halide electrolyte to obtain the cathode material; wherein the rotation speed of the second ball mill is lower than the rotation speed of the first ball mill.
[0016] In the preparation method described above, the rotation speed of the first ball mill is 100 rpm to 800 rpm; and / or, the milling time is 2 h to 10 h; and / or, the ball-to-material mass ratio of the first ball mill is (10 to 30): 1; and / or, the rotation speed of the second ball mill is 90 rpm to 250 rpm; and / or, the milling time is 1 h to 6 h; and / or, the ball-to-material mass ratio of the second ball mill is (5 to 20): 1.
[0017] In the preparation method described above, the rotation speed of the first ball mill is 300 rpm to 500 rpm; and / or, the first ball milling time is 2 h to 4 h; and / or, the rotation speed of the second ball mill is 90 rpm to 180 rpm; and / or, the second ball milling time is 2 h to 3 h.
[0018] This application also provides a positive electrode sheet, comprising the positive electrode material described in any one of the above claims, or the positive electrode material obtained by any one of the above preparation methods.
[0019] This application also provides a battery including the above-described positive electrode.
[0020] The battery described above is a solid-state battery, which includes a solid electrolyte layer, and the solid electrolyte layer includes a sulfide solid electrolyte; the sulfide solid electrolyte includes at least one of Li2S-P2S5 type sulfide solid electrolyte, thio-LISICON type sulfide solid electrolyte, sulfogermanium sulfide solid electrolyte and its amorphous derivatives.
[0021] This application also provides an electrical device, including the battery described above.
[0022] The cathode material provided in this application solves the core problem of interface mismatch between traditional cathode materials and solid electrolyte layers by functional differentiation and synergistic enhancement between the first and second coating layers, and addresses the issue from two dimensions: high-voltage stability and low interfacial impedance. This comprehensively suppresses multi-layer interfacial side reactions, reduces the overall impedance of the battery, and systematically optimizes the capacity and rate performance of solid-state batteries. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0024] In the conventional structure of solid-state batteries, the positive electrode, negative electrode, and solid electrolyte layer together constitute the basic unit. However, the inventors discovered during their research that the core bottleneck of electrochemical performance often lies not in the material itself, but in the interface. Taking sulfide solid electrolytes as an example, their stable electrochemical window is relatively narrow, and there is a significant electrochemical potential mismatch between them and the positive electrode material, especially high-voltage positive electrode materials. When the two are in direct physical contact during battery operation, the interface continuously triggers irreversible side reactions and gradually generates a high-resistance passivation layer. This interface degradation process directly leads to a surge in battery impedance and a sharp drop in capacity, causing a severe decline in rate capability and cycle performance, becoming a key obstacle restricting the improvement of the electrochemical performance of solid-state batteries.
[0025] To address this interfacial mismatch issue, the inventors first attempted a coating modification strategy, selecting a halide electrolyte with good compatibility with traditional solid electrolyte layers as a protective layer for the cathode material. However, experimental results showed that while this approach could alleviate the interfacial compatibility problem to some extent, the inherent high-voltage oxidation resistance of the halide electrolyte was insufficient, making it prone to self-decomposition under high-potential operating conditions. This failed to effectively mitigate side reactions at the cathode-electrolyte interface, and the passivation layer continued to accumulate during dynamic cycling.
[0026] To address this, the inventors attempted an alternative technical approach, using an oxide electrolyte with excellent high-voltage stability to coat the traditional cathode material. Experimental data showed that while this solution could withstand high operating voltages and maintain good stability at the cathode interface, new problems emerged: the solid-phase adhesion between the oxide electrolyte and the traditional solid electrolyte layer was poor, resulting in significant interfacial gaps. This caused the conduction channels to break during ion transport across the interface, and the interfacial impedance remained high, failing to achieve the expected performance improvement.
[0027] Through the aforementioned two-way exploration, the inventors realized that a single electrolyte material is difficult to simultaneously meet the dual requirements of high-voltage stability and low interfacial impedance. Only by breaking away from the inertia of optimizing a single material and instead focusing the research on how to achieve synergistic coupling of the two properties can the technical bottleneck of improving the performance of solid-state batteries be fundamentally broken.
[0028] Based on this, this application provides a positive electrode material, including a core, a first coating layer, and a second coating layer; the first coating layer is disposed on at least a portion of the surface of the core, and the second coating layer is disposed on at least a portion of the surface of the first coating layer away from the core; wherein, the first coating layer includes an oxide electrolyte, and the second coating layer includes a halide electrolyte.
[0029] The core can be a conventional cathode material in the art, such as lithium iron phosphate or lithium manganese iron phosphate; the oxide solid electrolyte can be a known oxide solid electrolyte material in the art, such as perovskite, garnet, or NASICON oxide electrolytes; the halide solid electrolyte can be a known halide solid electrolyte material in the art, such as Li3YCl6, Li3YBr6, or Li2ZrCl6; but is not limited to these.
[0030] The core technological advantage of this application stems from the functional differentiation and synergistic effect between the first and second coating layers, rather than a simple superposition of single materials. This dual-layer coating structure can simultaneously address the core challenge of interfacial mismatch between traditional cathode materials and solid electrolyte layers from two dimensions: chemical stability and physical adhesion. This comprehensively suppresses multi-layer interfacial side reactions, reduces the overall battery impedance, and systematically optimizes various electrochemical indicators of solid-state batteries.
[0031] Specifically, the oxide electrolyte in the first coating layer, with its inherently wide electrochemical window and excellent high-voltage withstand capability, can maintain structural and electrochemical stability within a high operating voltage range. This layer tightly coats the core surface, effectively isolating the core from direct contact with the second coating layer, thus suppressing the occurrence of oxidation side reactions at the positive electrode interface under high potentials. This completely eliminates the inherent defect of easy decomposition and failure due to insufficient high-voltage withstand capability when using a single halide electrolyte coating.
[0032] Meanwhile, the halide electrolyte in the second coating layer plays a crucial role in optimizing the compatibility of the external interface. It exhibits good chemical compatibility and interfacial wettability with traditional solid electrolyte layers such as sulfide-based layers, which can significantly improve the solid-solid interface adhesion between the cathode material and the solid electrolyte layer, effectively reduce the interfacial gap and lower the contact impedance, thus compensating for the problem of ion conduction obstruction caused by poor solid-phase adhesion when using a single oxide electrolyte coating.
[0033] It is worth noting that this double-layer coating structure is not a simple physical superposition of two functional layers, but rather the construction of a continuous ion transport pathway on the surface of the cathode material particles. The first coating layer ensures that ions efficiently escape from the core and enter the coating system, while the second coating layer ensures that ions smoothly migrate across the interface to the external solid electrolyte layer. Together, they achieve unimpeded ion conduction throughout the entire path of the core, coating layer, and solid electrolyte layer.
[0034] This structure can simultaneously optimize the stability of two key interfaces: the interface between the core and the first coating layer, and the interface between the second coating layer and the outer solid electrolyte layer, achieving a dual suppression of interfacial side reactions. This fundamentally alleviates the long-standing incompatibility between the cathode material and the solid electrolyte layer, effectively reduces irreversible capacity loss during charging and discharging, and significantly improves the first-cycle coulombic efficiency.
[0035] Based on the above mechanisms, the cathode material provided in this application, when applied to solid-state batteries, can effectively extend the cycle life of solid-state batteries while improving battery discharge capacity and fast-charging performance. Thanks to the excellent electrochemical stability and long-cycle stability of the double-layer coating structure, the usable capacity of solid-state batteries is effectively improved, and the long-cycle stability under high-temperature conditions is also significantly enhanced, demonstrating promising practical application prospects and commercial value.
[0036] In one specific embodiment, the mass percentage of the oxide electrolyte in the positive electrode material is less than or equal to 10%. The mass percentage of the oxide electrolyte in the positive electrode material may be, but is not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination thereof.
[0037] Specifically, by controlling the mass percentage of oxide electrolyte in the cathode material within the above-mentioned range, it is beneficial to achieve sufficient coverage and effective protection of the core surface by the first coating layer, and to avoid the problem that excessive oxide electrolyte will negatively affect the overall ion transport efficiency due to its relatively low ionic conductivity, thereby achieving a better balance between interface stability and ion conduction.
[0038] In one specific embodiment, the mass percentage of the halide electrolyte in the cathode material is less than or equal to 10%. The mass percentage of the halide electrolyte in the cathode material may be, but is not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination thereof.
[0039] Specifically, by controlling the mass percentage of halide electrolyte in the cathode material within the above-mentioned range, it is beneficial to form a good interface between the second coating layer and the external solid electrolyte layer. At the same time, it can also reduce the risk that excessive halide electrolyte will affect the overall structural stability due to its insufficient high voltage resistance, thus more effectively balancing the dual requirements of interface optimization and structural stability.
[0040] Furthermore, when the mass percentage of oxide electrolyte in the cathode material is 2% to 5%, a fully connected and uniformly distributed oxide electrolyte network can be formed within the first coating layer, ensuring rapid and continuous ion conduction between the core and the second coating layer. At the same time, the high potential tolerance of oxide electrolyte ensures that the first coating layer maintains structural integrity and chemical inertness during long-term high-voltage cycling, thereby further improving interface protection and ion conduction efficiency.
[0041] Furthermore, when the mass percentage of halide electrolyte in the cathode material is 2% to 5%, sufficient and complete ion migration channels can be constructed in the second coating layer, which maximizes the interfacial contact area between the halide electrolyte and the external solid electrolyte layer and optimizes the ion exchange efficiency. At the same time, it avoids the amplification of its own voltage withstand weakness due to excessive halide electrolyte content, ensuring that the double-layer coating structure performs better in both ion conduction and interface adaptation functions.
[0042] In one specific embodiment, the thickness of the first coating layer is 5 nm to 20 nm. The thickness of the first coating layer may be, but is not limited to, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, or any combination thereof.
[0043] In this application, the thickness of the first coating layer refers to the maximum thickness of the first coating layer. Specifically, by controlling the thickness of the first coating layer within the above-mentioned range, it is beneficial to ensure that the first coating layer has sufficient density and coverage integrity to isolate the direct contact between the core and the outside world, effectively suppressing the interface oxidation side reaction under high potential. It also avoids the problems of prolonged ion conduction path and limited core capacity caused by excessive thickness of the first coating layer, so as to achieve a better balance between interface protection effect and ion transport kinetics.
[0044] In one specific embodiment, the thickness of the second coating layer is 10 nm to 100 nm. The thickness of the second coating layer can be, but is not limited to, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any combination thereof.
[0045] The thickness of the second coating layer as defined in this application refers to the maximum thickness of the second coating layer. Specifically, by controlling the thickness of the second coating layer within the above-mentioned range, it is beneficial to form a sufficient and continuous interfacial contact between the second coating layer and the external solid electrolyte layer, thereby minimizing the ion conduction barrier caused by the interfacial gap, and avoiding unnecessary increase in interfacial impedance due to excessive coating layer thickness, thereby further promoting efficient and smooth conduction of ions during cross-interfacial migration.
[0046] In one specific implementation, the kernel's Dv50 is 3μm to 5μm. The kernel's Dv50 can be, but is not limited to, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, or any combination thereof.
[0047] Specifically, by controlling the core's Dv50 within the aforementioned range, it is beneficial to ensure that it has a suitable specific surface area to facilitate the uniform adhesion and complete coverage of the double-layer coating. It also allows for maintaining a reasonable packing density and interparticle contact state during the preparation of the cathode, thereby more effectively balancing the interfacial coating effect with the overall ion and electronic conduction performance of the cathode.
[0048] In one specific embodiment, the oxide electrolyte includes at least one of perovskite oxide electrolyte, garnet oxide electrolyte, NASICON oxide electrolyte, LISICON oxide electrolyte, and amorphous oxide.
[0049] Among them, the perovskite oxide electrolyte can be, for example, Li 3x La 2 / 3-x TiO3 (0.05≤x≤0.167) and La 0.5 Li 0.5 Ti 1-x Mx At least one of O3 (0.05≤x≤0.15, M selected from at least one of Al and Mg); garnet-type oxide electrolytes may be, for example, Li7La3Zr2O 12 Li 6.5 La3Zr 1.5 Ta 0.5 O 12 and Li 6.25 La3Zr2Al 0.25 O 12 At least one of them; the NASICON-type oxide electrolyte may be, for example, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 At least one of (PO4)3 and LiTi2(PO4)3; the LISICON type oxide electrolyte may be, for example, Li 14 Zn(GeO4)4, Li 3.6 Si 0.6 P 0.4 O4, Li 3.5 Zn 0.25 At least one of GeO4; the amorphous oxide may be, for example, at least one of lithium phosphorus oxynitride (LiPON), amorphous LiNbO3, and amorphous Li2SiO3.
[0050] Specifically, these materials all possess a wide electrochemical window and excellent high-voltage structural stability. They can be flexibly matched with different cathode materials according to actual needs, thereby providing more reliable inner high-voltage protection for the double-layer coating structure and ensuring long-term interfacial chemical inertness under high operating voltage.
[0051] In one specific embodiment, the halide electrolyte includes at least one of Li3MX6 type halide electrolyte, Li2MX4 type halide electrolyte, Li6MX8 type halide electrolyte, and amorphous halide.
[0052] Among them, the Li3MX6 type halide electrolyte can be at least one of Li3YCl6, Li3InCl6, Li3YBr6, Li3ErCl6, and Li3ScCl6; the Li2MX4 type halide electrolyte can be at least one of Li2ZrCl6, Li2CoCl4, Li2MgCl4, LiTaOCl4, and Li2MnCl4; the Li6MX8 type halide electrolyte can be at least one of Li6TaCl8, Li6NbCl8, and Li6MoCl8; and the amorphous halide can be at least one of amorphous Li3InCl6, amorphous Li3YCl6, and amorphous Li2ZrCl6.
[0053] Specifically, this type of material has good mechanical ductility and interfacial wetting properties, and can achieve tight solid-phase bonding with various traditional solid electrolyte systems such as sulfide-based materials. This provides a more ideal outer layer interface adaptation function for the double-layer coating structure, thereby further reducing the cross-interface ion migration barrier and achieving further improvement in battery performance.
[0054] In one specific embodiment, the core includes at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium-rich manganese-based materials.
[0055] Specifically, these materials all have the advantages of high specific capacity and operating voltage platform. Through the synergistic protection of the double-layer coating structure, the interfacial compatibility between them and the solid electrolyte layer is fundamentally improved, and the high capacity characteristics of the materials themselves are fully released, thereby providing more continuous and stable energy output for solid-state batteries.
[0056] When testing the battery, it can be disassembled after discharge. The positive electrode sheet is then removed, embrittled with liquid nitrogen, and gently ground to break the binder fiber network (e.g., PTFE) and release the positive electrode material particles. The powder is dispersed in an anhydrous and oxygen-free nonpolar solvent (e.g., n-heptane). Utilizing the density difference between the positive electrode material and other components, the positive electrode material preferentially settles to the bottom through low-speed centrifugation or static sedimentation. The supernatant is discarded, and the washing and sedimentation are repeated several times. After vacuum drying, the positive electrode material is obtained.
[0057] The relevant parameters of the cathode material are then tested through the following process:
[0058] 1. X-ray diffraction (XRD) is used to identify crystal structures. Transmission electron microscopy (HRTEM) can directly observe the lattice fringes of the two coating layers. Combined with selected area electron diffraction or fast Fourier transform, it can be determined whether each layer is crystalline or amorphous, and the phase can be determined.
[0059] 2. The content of all metal elements can be determined simultaneously using ICP-OES / MS. Combined with the known chemical formula of the electrolyte, the mass of the electrolyte in each layer can be calculated by the element molar ratio. The remaining mass is the mass of the core.
[0060] 3. Ultrathin sections are prepared by cutting cathode material particles using focused ion beam (FIB). Under scanning transmission electron microscopy (HAADF-STEM), the thickness of the two coating layers can be directly measured by utilizing the contrast difference caused by different atomic numbers. EDS line scanning is used to define the interface by elemental abrupt changes. XPS depth profiling can also be used to obtain elemental content-depth curves through argon ion etching, and the thickness can be calculated after calibration.
[0061] 4. The cross-section of the cathode material particles can be prepared by focusing ion beam (FIB) cutting, and the Dv50 of the core can be measured by SEM.
[0062] This application also provides a method for preparing the aforementioned cathode material, comprising the following steps: first ball milling the core and oxide electrolyte to obtain an intermediate; second ball milling the intermediate and halide electrolyte to obtain the cathode material; wherein the rotation speed of the second ball mill is lower than that of the first ball mill.
[0063] The above preparation method achieves controllable preparation of a double-layer coating structure through stepwise ball milling combined with gradient speed control. Specifically, the first ball milling uses a high speed, utilizing the high-energy impact force of the milling beads to induce an embedding-cold welding effect in the oxide electrolyte particles, thereby firmly anchoring them to the core surface and forming a dense and strongly adherent first coating layer. This ensures that the oxide layer is not easily detached during subsequent processing and long-term battery cycling, providing continuous and reliable high-voltage protection for the core.
[0064] The second ball milling uses a lower rotational speed than the first. This low-energy ball milling condition fully utilizes the inherent low yield strength of the halide electrolyte material, which preferentially undergoes plastic deformation rather than brittle fracture under mechanical friction. This allows it to spread evenly on the surface of the first coating layer in a layered manner, and the van der Waals forces and surface energy drive the formation of a continuous and complete second coating layer. The lower rotational speed avoids excessive mechanical force that could cause impact peeling of the formed first coating layer, and also prevents the halide layer from losing its interfacial integrity due to excessive fragmentation.
[0065] The core of this preparation method lies in the energy-level design of two ball milling processes. High-energy ball milling ensures the robustness and density of the inner oxide coating, while low-energy ball milling balances the uniformity and structural integrity of the outer halide coating. The synergy of these two processes ensures the integrity of the double-layer coating structure and the interfacial bonding force in the final product. This allows the prepared cathode material to fully utilize the high-voltage protection function of the oxide layer and the interfacial compatibility function of the halide layer when applied to solid-state batteries, thereby guaranteeing the stable performance of the battery's electrochemical properties.
[0066] The double-layer coating can be constructed by relying on two-step mechanical ball milling, without the need for complex liquid phase treatment and high-temperature calcination processes. The operation process is simple, efficient, and easy to mass-produce in industrial applications.
[0067] In one specific embodiment, the rotational speed of the first ball mill is 100 rpm to 800 rpm. The rotational speed of the first ball mill may be, but is not limited to, 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, or any combination thereof.
[0068] Specifically, by controlling the rotational speed of the first ball mill within the aforementioned specific range, sufficient mechanical energy can be provided to the oxide electrolyte particles to achieve effective anchoring with the core surface. Under this rotational speed condition, the impact force generated by the milling beads is sufficient to enable the oxide particles to form a firmly attached initial coating layer, while avoiding excessive breakage of the oxide particles or damage to the core material structure due to excessive rotational speed, thereby further improving the density and structural integrity of the first coating layer.
[0069] In one specific implementation, the first ball milling time is 2h to 10h. The first ball milling time can be, but is not limited to, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any combination thereof.
[0070] Specifically, by controlling the first ball milling time within the aforementioned specific range, it is possible to ensure sufficient mixing and interaction time between the oxide electrolyte and the core, allowing the oxide particles to gradually and uniformly anchor onto the core surface under continuous mechanical impact. At the same time, it is possible to avoid introducing unnecessary impurities or adversely affecting the crystal structure of the material due to excessively long ball milling time, thus balancing the coating effect and process efficiency.
[0071] In one specific embodiment, the ball-to-material mass ratio of the first ball mill is (10~30):1. The ball-to-material mass ratio of the first ball mill can be, but is not limited to, 10, 15, 20, 25, 30, or any combination thereof.
[0072] Specifically, by controlling the ball-to-material mass ratio in the first ball mill within the aforementioned specific range, it is beneficial to ensure sufficient grinding media to provide the necessary mechanical energy input, while also avoiding unnecessary energy waste and equipment wear caused by an excessively high ball-to-material ratio. Under this ratio, the oxide electrolyte particles can obtain ample collision opportunities between the grinding balls and the material, achieving a more efficient and uniform coating effect, and exhibiting good process economy.
[0073] In one specific embodiment, the rotational speed of the second ball mill is 90 rpm to 250 rpm. The rotational speed of the second ball mill can be, but is not limited to, 90 rpm, 150 rpm, 200 rpm, 250 rpm, or any combination thereof.
[0074] Specifically, by controlling the rotational speed of the second ball mill within the aforementioned specific range, a more moderate mechanical frictional force can be provided to the halide electrolyte to induce its plastic deformation and layered spreading. This rotational speed condition can both drive the halide particles to spread fully on the surface of the first coating layer to form a continuous and complete outer coating, and avoid excessive mechanical force causing impact peeling of the anchored first coating layer, thus more effectively protecting the integrity of the inner layer structure.
[0075] In one specific implementation, the second ball milling time is 1 hour to 6 hours. The second ball milling time can be, but is not limited to, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or any combination thereof.
[0076] Specifically, by controlling the second ball milling time within the aforementioned specific range, it is possible to ensure sufficient mixing and spreading time between the halide electrolyte and the intermediate, allowing the halide particles to gradually complete plastic deformation and spread evenly on the surface of the first coating layer under continuous low-energy mechanical action. At the same time, it is possible to avoid unnecessary decomposition of the halide material or the introduction of additional impurities due to excessively long ball milling.
[0077] In one specific embodiment, the ball-to-material mass ratio of the second ball mill is (5~20):1. The ball-to-material mass ratio of the second ball mill can be, but is not limited to, 5, 10, 15, 20, or any combination thereof.
[0078] Specifically, by controlling the ball-to-material mass ratio of the second ball mill within the aforementioned specific range, it is possible to ensure that the halide electrolyte receives sufficient mechanical action to complete plastic spreading, while avoiding excessive crushing of the outer coating structure or accidental peeling of the inner coating layer due to an excessively high ball-to-material ratio, thus providing better process controllability.
[0079] Furthermore, when the rotation speed of the first ball mill is 300 rpm to 500 rpm, the oxide electrolyte particles can achieve more uniform dispersion and arrangement on the core surface, forming a continuous and uniformly thick dense coating layer, which provides a more ideal basic interface for the uniform growth of the subsequent second coating layer.
[0080] Furthermore, when the first ball milling time is 2 to 4 hours, the anchoring degree of the oxide electrolyte particles on the core surface reaches a better state, and the density and coverage of the coating layer are further improved. This time range also helps to promote the formation of better interfacial bonding between the core and the oxide layer, so that the first coating layer maintains structural stability during subsequent low-energy ball milling and long-term battery cycling, and is not prone to peeling or cracking.
[0081] Furthermore, when the rotation speed of the second ball mill is 90 rpm to 180 rpm, the halide electrolyte exhibits better plastic flow behavior under the action of mechanical friction, which can form a more uniform and complete outer coating on the surface of the first coating layer. This ensures that the double-layer coating structure maintains structural synergy in subsequent applications and fully utilizes their respective interface optimization functions.
[0082] Furthermore, when the second ball milling time is 2h~3h, the halide electrolyte layer can achieve a better spreading state and coverage integrity on the surface of the first coating layer, thereby minimizing the resistance to interfacial ion transport.
[0083] This application also provides a positive electrode sheet, including the aforementioned positive electrode material or the positive electrode material obtained by the aforementioned preparation method. This positive electrode sheet has advantages corresponding to the aforementioned positive electrode material, which will not be elaborated further here.
[0084] The positive electrode sheet of this application specifically includes a positive current collector and a positive active layer formed of positive electrode material disposed on the surface of the positive current collector.
[0085] In the specific preparation of the positive electrode sheet, for example, the positive electrode material, solid electrolyte, conductive agent and fiberizable binder of this application can be mixed under solvent-free dry conditions, and the binder can be fiberized in situ by mechanical shearing force to form a uniform mixture wrapped by a fiber network; the mixture is pressed into a self-supporting film by heated rollers, and then the self-supporting film is hot-pressed and composited with the positive electrode current collector to obtain a dry positive electrode sheet.
[0086] The positive electrode active layer comprises, by weight percentage, 70-95 wt% positive electrode material, 4-25 wt% sulfide solid electrolyte, 0.5-5 wt% conductive agent and 0.5-5 wt% fiberizable binder.
[0087] The positive electrode current collector can be made of at least one of carbon-coated aluminum foil, porous carbon paper, or metal mesh; the sulfide solid electrolyte includes at least one of glassy Li2S-P2S5 type, thio-LISICON type, silver-germanium sulfide type, and its amorphous derivatives; the conductive agent can be at least one of carbon black, carbon nanotubes, and graphene; the fiberizable binder can be selected from at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, and ultra-high molecular weight polyethylene, preferably polytetrafluoroethylene.
[0088] This application also provides a battery including the aforementioned positive electrode sheet, which has advantages corresponding to the aforementioned positive electrode material, which will not be elaborated further here.
[0089] The battery described in this application can be a liquid battery or a solid-state battery; no specific limitation is made here. The battery described in this application can be any of the following: a battery cell, a battery module, or a battery pack.
[0090] A battery module typically comprises multiple individual battery cells, which are connected to form the battery module. These batteries can be electrically connected using methods conventional in the art, such as series connection, parallel connection, or a combination of these connection methods, without any particular limitation.
[0091] The battery pack includes the aforementioned individual battery cells or battery modules. The battery pack can be installed as a whole module onto electrical equipment through its mechanical interface and high-voltage connector.
[0092] Taking a solid-state single-cell battery as an example, in addition to the aforementioned positive electrode sheet, it also includes a negative electrode sheet and a solid electrolyte layer. This application does not strictly limit the negative electrode material in the negative electrode sheet. Taking a lithium-ion battery as an example, it can be at least one of the negative electrode materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrodes), and tin-based negative electrode materials (mainly including tin and tin alloys).
[0093] In the specific preparation of solid-state single-cell batteries, for example, materials including solid electrolytes can be dispersed in xylene solvent to obtain solid electrolyte slurry; the solid electrolyte slurry is coated on the surface of a metal substrate and dried to obtain a solid electrolyte layer; the solid electrolyte layer is rolled and transferred onto a negative electrode sheet, and the substrate is peeled off; the negative electrode sheet, electrolyte layer, and positive electrode sheet are stacked in the order of stacking to form a cell, and then isostatic pressing is performed to obtain a solid-state single-cell battery.
[0094] In one specific embodiment, the battery is a solid-state battery, which includes a solid electrolyte layer, and the solid electrolyte layer includes a sulfide solid electrolyte, which includes at least one of Li2S-P2S5 type sulfide solid electrolyte, thio-LISICON type sulfide solid electrolyte, sulfogermanium sulfide solid electrolyte and its amorphous derivatives.
[0095] These electrolyte materials all possess excellent ion conductivity and exhibit superior interfacial chemical compatibility and physical adhesion with the cathode material of this application. Through synergistic matching, a stable and efficient ion transport channel can be established at the interface between the cathode sheet and the solid electrolyte layer, effectively suppressing the induction and accumulation of interfacial side reactions, further reducing the full-cell interfacial impedance, and thus ensuring that the solid-state battery continuously outputs excellent capacity retention and rate performance under high voltage and long-cycle conditions.
[0096] This application also provides an electrical device including the aforementioned battery, which has advantages corresponding to the aforementioned positive electrode material, which will not be elaborated further here.
[0097] The electrical equipment used in this application can be conventional electrical equipment in the field, such as power equipment (e.g., electric vehicles, electric cars, car chassis), electronic equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., without any particular limitation.
[0098] The cathode material provided in this application will be described in detail below through specific embodiments.
[0099] Unless otherwise specified, the reagents, materials and instruments used in the following examples are all conventional reagents, materials and instruments in the art, and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0100] Example 1
[0101] The preparation method of the cathode material in this embodiment includes the following steps:
[0102] The kernel (Dv50 is 4μm Li) 1.2 Ni 0.35 Mn 0.65 O2) and oxide electrolytes (Li 1.5 Al 0.3 Ti 1.7 (PO4) 2.8 (SiO4) 0.2 The mixture was ball-milled at 400 rpm for 3 hours to obtain an intermediate; subsequently, the intermediate and a halide electrolyte (Li) were added. 2.9 In 0.9 Zr 0.1 The mixture of Cl6 and other components was ball-milled at 150 rpm for 2 hours to obtain the cathode material, which, by mass percentage, comprised 94% core, 3% oxide electrolyte, and 3% halide electrolyte.
[0103] Examples 2 to 10 differ from Example 1 in that the selection and proportion of the core, oxide electrolyte, and halide electrolyte, as well as the rotation speed and time of the first and second ball mills, are different. For details, please refer to Table 1. Except for the differences shown in Table 1, the remaining steps and conditions are the same as in Example 1.
[0104] Table 1 Comparison of Preparation Methods
[0105]
[0106] Comparative Example 1
[0107] The cathode material in this comparative example is the core of Example 1.
[0108] Comparative Example 2
[0109] The preparation method of the comparative example cathode material includes the following steps:
[0110] The kernel (Dv50 is 4μm Li) 1.2 Ni 0.35 Mn 0.65 O2) and halide electrolytes (Li 2.9 In 0.9 Zr 0.1 The mixture of Cl6 and other components was ball-milled at 150 rpm for 2 hours to obtain the cathode material, which, by mass percentage, comprised 97% of the core and 3% of the halide electrolyte.
[0111] Comparative Example 3
[0112] The preparation method of the comparative example cathode material includes the following steps:
[0113] The kernel (Dv50 is 4μm Li) 1.2 Ni 0.35 Mn 0.65 O2) and oxide electrolytes (Li 1.5 Al 0.3 Ti 1.7 (PO4) 2.8 (SiO4) 0.2 The mixture was ball-milled at 400 rpm for 3 hours to obtain the positive electrode material, which, by mass percentage, included 97% core and 3% oxide electrolyte.
[0114] Comparative Example 4
[0115] The preparation method of the comparative example cathode material includes the following steps:
[0116] The kernel (Dv50 is 4μm Li) 1.2 Ni 0.35 Mn 0.65O2) and halide electrolytes (Li 2.9 In 0.9 Zr 0.1 The mixture was stirred with Cl6 and ball-milled at 400 rpm for 3 hours to obtain an intermediate; subsequently, the intermediate was mixed with an oxide electrolyte (Li... 1.5 Al 0.3 Ti 1.7 (PO4) 2.8 (SiO4) 0.2 The mixture was ball-milled at 150 rpm for 2 hours to obtain the positive electrode material, which, by mass percentage, included 94% core, 3% oxide electrolyte, and 3% halide electrolyte.
[0117] Experimental Example 1
[0118] 1. The thicknesses of the first and second coating layers in the cathode materials of the examples and comparative examples were measured, and the test results are shown in Table 2; wherein,
[0119] The test employed a focused ion beam (FIB) to cut along the cross-sectional direction of the cathode material particles, preparing thin-film samples with uniform thickness. High-angle annular dark-field (HAADF) images of the thin-film cross-section were acquired using transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDS) line scanning analysis was performed in the radial direction of the cross-section. The thickness of the first coating layer was determined based on the EDS signal distribution width of the characteristic metal elements (such as Nb, Zr, Ta, etc.) contained in the inner layer of the oxide solid electrolyte. The thickness of the second coating layer was determined based on the EDS signal distribution width of the characteristic halogen elements (such as Cl, Br, etc.) contained in the outer layer of the halide solid electrolyte. Measurements were taken from no fewer than three different locations for each particle, and the arithmetic mean was used as the coating thickness of that layer.
[0120] 2. The positive electrode materials of the examples and comparative examples are assembled into positive electrode sheets, and then assembled with negative electrode sheets and solid electrolyte layers to form solid-state batteries; the specific preparation process is as follows:
[0121] 1) The positive electrode material, solid electrolyte (LPSCl), conductive agent (Super P), and fiberizable binder (PTFE) are mixed at high speed under solvent-free conditions in a mass ratio of 70:20:5:5, so that the fiberizable binder is fiberized in situ to form a uniform mixture wrapped with a fiber network; the mixture is rolled between heated rollers to form a self-supporting positive electrode film, and then the self-supporting positive electrode film is hot-pressed and compounded with the positive electrode current collector (aluminum foil), and the positive electrode sheet is obtained after slitting;
[0122] 2) The negative electrode material (graphite), solid electrolyte (LPSCl), conductive agent (carbon black) and binder (PVDF) are dispersed in a solvent (xylene) at a mass ratio of 60:30:5:5 to obtain a negative electrode slurry; the negative electrode slurry is coated on both surfaces of the negative electrode current collector (copper foil), and after drying, cold pressing and slitting, a negative electrode sheet is obtained;
[0123] 3) Disperse the solid electrolyte (LPSCl) and binder (PVDF) in a solvent (xylene) at a mass ratio of 90:10 to obtain a solid electrolyte slurry; coat the solid electrolyte slurry onto the surface of an aluminum foil substrate and dry it to obtain an electrolyte layer;
[0124] 4) Roll transfer the electrolyte layer onto the negative electrode sheet and peel off the aluminum foil substrate; stack the negative electrode sheet, electrolyte layer and positive electrode sheet in the order of negative electrode sheet, electrolyte layer and positive electrode sheet to form a cell, and then perform isostatic pressing at 500 MPa to obtain the battery.
[0125] Electrochemical tests were performed on the solid-state battery, and the results are shown in Table 2; among them,
[0126] First discharge capacity test: At 25℃, place the battery on a charge-discharge tester and charge it at a constant current and constant voltage (CC-CV) rate of 0.1C. The charging cutoff voltage is 4.6V, and the constant voltage is charged to the cutoff current of 0.05C. After standing for 10 minutes, discharge it at a constant current rate of 0.1C. The discharge cutoff voltage is 2.8V. Record the total discharge capacity of this discharge process, which is the first discharge capacity.
[0127] First discharge efficiency test: Based on the data obtained from the first charge and discharge test above, calculate the ratio of the first discharge capacity to the first charge capacity. The result is expressed as a percentage, which is the first coulomb efficiency (first discharge efficiency).
[0128] 1C cycle capacity retention test: At 25℃, the battery is charged and discharged at a 1C rate. The percentage of the discharge capacity after the 100th cycle relative to the first discharge capacity is calculated, which is the capacity retention rate at that rate.
[0129] Table 2 Performance Test Comparison Table
[0130]
[0131] In the comparative example, the coating layer that contacts the kernel is designated as the first coating layer, and the coating layer that does not contact the kernel is designated as the second coating layer.
[0132] As can be seen from Tables 1 and 2, the cathode material of this application, when applied to the cathode sheet, can effectively improve the capacity performance of solid-state batteries, improve the rate performance stability during cycling, and promote the development of solid-state batteries towards longer cycle life.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A positive electrode material, characterized in that, It includes a core, a first coating layer, and a second coating layer; the first coating layer is disposed on at least a portion of the surface of the core, and the second coating layer is disposed on at least a portion of the surface of the first coating layer away from the core; The core comprises at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium-rich manganese-based materials; the first coating layer comprises an oxide electrolyte, and the second coating layer comprises a halide electrolyte.
2. The cathode material according to claim 1, characterized in that, The oxide electrolyte has a mass percentage content of less than or equal to 10% in the positive electrode material; and / or, The mass percentage of the halide electrolyte in the cathode material is less than or equal to 10%.
3. The cathode material according to claim 1 or 2, characterized in that, The oxide electrolyte has a mass percentage content of 2% to 5% in the positive electrode material; and / or, The halide electrolyte has a mass percentage content of 2% to 5% in the cathode material; and / or, The thickness of the first coating layer is 5 nm to 20 nm; and / or, The thickness of the second coating layer is 10nm~100nm.
4. The cathode material according to claim 3, characterized in that, The kernel's Dv50 is 3μm~5μm.
5. The cathode material according to any one of claims 1, 2, and 4, characterized in that, The oxide electrolyte includes at least one of perovskite oxide electrolyte, garnet oxide electrolyte, NASICON oxide electrolyte, LISICON oxide electrolyte, and amorphous oxide; and / or, The halide electrolyte includes at least one of Li3MX6 type halide electrolyte, Li2MX4 type halide electrolyte, Li6MX8 type halide electrolyte, and amorphous halide.
6. A method for preparing the cathode material according to any one of claims 1-5, characterized in that, The process includes the following steps: first ball milling the core and the oxide electrolyte to obtain an intermediate; second ball milling the intermediate and the halide electrolyte to obtain the cathode material; wherein the rotational speed of the second ball milling is lower than that of the first ball milling.
7. The preparation method according to claim 6, characterized in that, The rotational speed of the first ball mill is 100 rpm to 800 rpm; and / or, The first ball milling time is 2 hours to 10 hours; and / or, The ball-to-material mass ratio of the first ball mill is (10~30):1; and / or, The rotational speed of the second ball mill is 90 rpm to 250 rpm; and / or, The second ball milling time is 1 hour to 6 hours; and / or, The ball-to-material mass ratio of the second ball mill is (5~20):
1.
8. The preparation method according to claim 6 or 7, characterized in that, The rotational speed of the first ball mill is 300 rpm to 500 rpm; and / or, The first ball milling time is 2h~4h; and / or, The rotational speed of the second ball mill is 90 rpm to 180 rpm; and / or, The second ball milling time is 2 to 3 hours.
9. A positive electrode plate, characterized in that, This includes the cathode material according to any one of claims 1-5, or the cathode material obtained by the preparation method according to any one of claims 6-8.
10. A battery, characterized in that, Includes the positive electrode sheet as described in claim 9.
11. The battery according to claim 10, characterized in that, The battery is a solid-state battery, which includes a solid electrolyte layer, and the solid electrolyte layer includes a sulfide solid electrolyte; the sulfide solid electrolyte includes at least one of Li2S-P2S5 type sulfide solid electrolyte, thio-LISICON type sulfide solid electrolyte, sulfosilver germanite type sulfide solid electrolyte and its amorphous derivative.
12. An electrical appliance, characterized in that, Includes the battery as described in claim 10 or 11.
